ENVIRONMENTAL GEOCHEMISTRY AND ECOLOGICAL RISK OF VANADIUM POLLUTION IN PANZHIHUA MINING AND SMELTING AREA, SICHUAN, CHINA - Teng Ya.; Ni Sh.; Zhang Ch.; Wang J.; Lin X.; Huang Y. (My University, 2006)
Vanadium is a trace element widely distributed in the Earth’s crust. Naturally high levels of vanadium are recognized mainly in basic rocks and minerals, particularly in titaniferous magnetite. And the anthropogenic sources of vanadium include fossil fuel combustion and wastes including steel-industry slags. In the last few years, the authors have made investigations and assessments on the environmental geochemistry and ecological risk of vanadium in the Panzhihua mining and smelting area. In the study area, anthropogenic vanadium resulted from mining, extracting and smelting of V-Ti magnetite; vanadium pollution of topsoil and sediments occurs mainly in the mining and extracting area, smelting area, slag dumping area, tailing dam and coal mining area. In the soil, the chemical speciation of vanadium shows: insoluble residue > organically bound > Fe (amorphous) oxide-bound > Mn oxide-bound > soluble component. Vanadium pollution can cause potential harmful effects on ecological systems, and lead to animal poisoning and human disease. So vanadiam pollution should be monitored on a regular basis in the Panzhihua area.
Keywords: VANADIUM; ENVIRONMENTAL GEOCHEMISTRY; ECOLOGICAL RISK; PANZHIHUA AREA